The service revolution and its marketing implications: service logic vs service-dominant logic. Issue 3 (6th May 2014) - Grönroos, Christian; Gummerus, Johanna
Abstract : Purpose: – The purpose of this conceptual paper is to analyse the implications generated by a service perspective. Design/methodology/approach: – A conceptual analysis of two approaches to understanding service perspectives, service logic (SL) and service-dominant logic (SDL), reveals direct and indirect marketing implications. Findings: – The SDL is based on a metaphorical view of co-creation and value co-creation, in which the firm, customers and other actors participate in the process that leads to value for customers. The approach is firm-driven; the service provider drives value creation. The managerial implications are not service perspective-based, and co-creation may be imprisoned by its metaphor. In contrast, SL takes an analytical approach, with co-creation concepts that can significantly reinvent marketing from a service perspective. Value gets created in customer processes, and value creation is customer driven. Ten managerial SL principles derived from these analyses offer theoretical and practical conclusions with the potential to reinvent marketing. Research limitations/implications: – The SDL can direct researchers' and managers' views towards complex value-generation processes. The SL can analyse this process on a managerial level, to derive customer-centric, service perspective-based opportunities to reinvent marketing. Practical implications: – The analysis and principles help marketing break free from offering only value propositions and become an organisation-wide responsibility. Firms must organise service-influenced marketing and create a customer focus among all employees, beyond conventional marketing. Originality/value: – A service perspective on business has key managerial implications and enables researchers and managers to find new, customer-centric, service-influenced marketing approaches.